UTILIZACIÓN DE HARINA Musa Acuminata PARA EL DESARROLLO DE BIOPELICULAS INCORPORADAS CON ACEITES ESENCIALES Origanum Vulgare Y Citrus x Sinensis”. - Tualombo Gagñay, Jeniffer Amanda (2020)
Due to the environmental pollution caused by the human being as a result of the massive use of synthetic plastic, usually used as packaging by all industries is the purpose of this research is to develop a new option for biodegradable wrapping to replace plastics made from banana flour (Musa acuminata) incorporated with essential oils of oregano (Origanum vulgare L.) and orange (Citrus x sinensis) using the technique casting; as an alternative to reduce the environmental impact due to its easy degradation. Therefore, six treatments were designed (T1. T2. T3. T4. T5, T6) based on banana flour incorporated with essential oil of oregano (AEO) and orange (NEA) at different concentrations (0.3, 0.6, 0.9%) using the casting technique (monolayer). Physicochemical and mechanical properties were evaluated to determine the biofilms quality, statistically establishing the optimal formulation through an analysis of variance (ANOVA). The cost-benefit of the best treatment of the developed biofilms calculated. The treatment T1 (AEO at 0.3%) determines the ideal combination because it presents better characteristics based on resistance to water, a maximum value of 31.26 minutes. A minimum humidity percentage of 0.3% was evidence, as well as a pH of 6 (slightly acidic), acceptable results according to NTE INEN- ISO 712 and NTE INEN 526; finally, a thickness of 0.25 mm, proper value by the NTE INEN-ISO 4593. Regarding the financial evaluation, the project is feasible, cost-benefit of $ 1.30 obtained in biodegradable packaging in mortadella production.